Factors Influencing Decisions to Purchase Fuel Oil at PT. Widya Waskita Wijaya - Badruddin, Badruddin; Octavia, Ayu Nurafni (Economics and Business Solutions Journal, 2024)
In a rapidly evolving technological landscape, industries, including those distributing essential goods such as fuel oil (BBM), must adapt to maintain efficiency, BBM is essential for daily mobility and industrial activities. This study examines the influence of price perception, product quality, and service quality on fuel purchasing decisions. Competitive market dynamics require companies to understand and strategically respond to competitors' tactics to improve their market position. PT Widya Waskita Wijaya's recovery from declining revenue in 2022 to high revenue in 2023, although still lagging behind competitors such as PT AKR and PT Shell, underscores the importance of consumer perceptions of fuel prices and product quality. Compliance with international and national standards ensures fuel quality and prevents vehicle damage, while service quality at gas stations affects consumer satisfaction. This study uses a quantitative approach, analyzing secondary data from 2020-2022 and consumer surveys, using multiple linear regression to test the relationship between price perception, product quality, service quality, and purchasing decisions. The results show that price perception affects purchasing decisions, product quality affects purchasing decisions, and service quality affects purchasing decisions. Simultaneously, perceptions of price, product quality and service quality influence purchasing decisions, indicating high consumer trust and satisfaction with PT Widya Waskita Wijaya's BBM products and services